ТУПРОҚНИ БОЙИТИШДА БИОТИК ЧИҚИНДИЛАРДАН ФОЙДАЛАНИШНИНГ ЎСИМЛИКЛАР ҲОСИЛДОРЛИГИГА ТАЪСИРИ (Scientific journal of the Fergana State University, 2023)
In this article set forth the meaning of the organic mass the (biological) biotic group in the rise of fertile soil, their role of concentrated cultured plants and microorganisms of soil.